A Systematic Review of Research Trends on Creative Thinking Skills in Chemistry Learning (2015-2024) - Nurul Hidayah; Wahyuni Arafani; Aris Doyan; Syarful Annam (Indonesian Journal of STEM Education, 2024)
Creative thinking skills are one of the aspects that are part of 21st-century skills. However, students' creative thinking ability is still relatively low so it is very important to improve this ability. This study aims to identify and analyse research trends in creative thinking skills in chemistry learning from 2015-2024. This research method is descriptive and analytical, with data obtained from documents indexed by Google Scholar using Publish or Perish and Dimension.ai. The research procedure uses PRISMA guidelines and data analysis is carried out using bibliometric analysis assisted by VOS viewer software. The results of the analysis show that the trend of research on creative thinking skills in chemistry learning has increased and decreased during the period 2015-2024. The increase in the number of publications occurred from 2015 to 2018, then decreased in 2019, and increased again from 2020-2021. However, the trend decreased again in 2022-2023. There are many documents in the form of Chapters, Articles, Edited Books, monographs, Proceedings, and Preprint that discuss research on creative thinking skills in chemistry learning. Keyword analysis shows that the most frequently occurring terms in this research include Chemistry Learning 280 times and Creative Thinking 204 times. This trend reflects the growing attention to creative thinking in chemistry learning and indicates the need for further efforts to improve research and applications in this area.